Nośność Graniczna i Kształtowanie Wytrzymałościowe Płyt Pierścieniowych - Z. Mróz (Engineering Transactions)
In the first part of this paper, the limit load of annular plates is analysed for any transverse load q acting in one direction and for various edge supports. The cases treated are those of outer or inner edge simply supported or clamped or having both edges simply supported. The Coulomb-Tresca yield condition and the rigid-plastic model are assumed for q = const. The results are represented in graphical form. The second part of the paper is devoted to the minimum weight design. The problem is stated as a variational problem. The limit curve is assumed in the form of a polygon with rounded corners. The conditions for (strong) minimum value of the functional expression obtained are examined. It is seen that the condition of constant mean energy dissipation leads to a minimum for the corners A, F, C, D. The general considerations are illustrated by examples of plates subjected to the action of a load q= const and for various types of support.